Fully self-justifiable outcomes - Francesc Dilmé (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2025)
An equilibrium outcome of a game in extensive form is fully self-justifiable if it is supported by justifiable equilibria (McLennan, 1985) regardless of the order in which actions implausible under the given outcome are excluded. We show that the set of fully self-justifiable outcomes is non-empty and contains the set of sequentially stable outcomes (Dilmé, 2024). In signaling games, fully self-justifiable outcomes pass all the selection criteria in Cho and Kreps (1987). Full self-justifiability allows for the systematic use of the logic of selection criteria in signaling games to select equilibria in any finite extensive form game.
Keywords: C72; C73; 330; Justifiable equilibria; selection criteria